Media Pembelajaran Matematika bagi Siswa Kelas 3 SD Berbasis Android - Lana Gulam Pandita; Melinda, Linda Daniati; Hadiansyah Ma'sum (Darma Abdi Karya, 2022)
With the COVID-19 pandemic, the learning process has changed. Where previously the learning process took place face-to-face, learning has changed to online. With the change in learning methods from face-to-face (offline) to online, many learning patterns have also changed, such as the use of Android for the learning and teaching process. In this research, the author focuses on the use of Android in the field of learning. The use of android is becoming more widely used by students or schoolgirls, be it high school, junior high school, even elementary school students.